PENGARUH PENGUNGKAPAN INTELLECTUAL CAPITAL TERHADAP COST OF EQUITY CAPITAL Studi Empiris pada Perusahaan yang Terdaftar di Indeks LQ45 Bursa Efek Indonesia Tahun 2012 - Wulandari Wulandari; Andri Prastiwi (Diponegoro Journal of Accounting, 2014)
The purpose of this study is to analyze empirically the impact of Intellectual Capital (and its three aspects : Human Capital, Structural Capital & Relational Capital) disclosure and Cost of Equity Capital (COEC). This study used Intellectual Capital disclosure as independent variable and Cost of Equity Capital as dependent variable. This study also used firms size, beta, leverage, market value to book value ratio, and industry type as control variables.             The sample used in this study was the secondary data from Bursa Efek Indonesia (BEI/Indonesia Exchange Stock), i.e. the annual report of companies that listed in Indeks LQ45 BEI in 2012. The sample was taken using the method of purposive sampling, and those meeting the selection criteria were also taken. The sample used was contain of 44 firms.            The statistics method used was multiplied analysis linear regression, with hypotheses testing of statistic t and F tests. The result show: (1) agregatly, Intellectual Capital disclosure has a negative significant impact on Cost of Equity Capital (COEC).  (2) Human Capital disclosure has a negative significant impact on Cost of Equity Capital (COEC). (3) Structural Capital disclosure has a negative significant impact on Cost of Equity Capital (COEC). (4) Relational Capital disclosure has no significant impact on Cost of Equity Capital (COEC).